Peran Olahraga Dalam Meningkatkan Kesehatan Mental - Puput Mulyono; Singgih Purnomo (Jurnal Mahasiswa Ilmu Kesehatan, 2023)
Exercise has many physical benefits, including reducing stress. People who exercise regularly tend to appear more relaxed and cheerful, making them more resilient to physical and emotional stress. This is especially relevant for students who may experience stress due to the change in learning style from junior high school to higher education. The purpose of this study was to investigate the relationship between exercise habits and stress levels in the community of area X. This study used a cross-sectional design and used two basic instruments: the Exercise Habits Questionnaire and the DASS-42. This questionnaire was specifically intended for all adults aged 25-55 years, totaling 96 people and respondents were sampled and analyzed using the Chi Square test. The results showed that 38 respondents (39.6%) exercised regularly, while 58 respondents (60.4%) did not exercise. A total of 57 respondents (59.4%) reported normal stress levels, while 9 respondents (9.4%) reported mild stress levels, 13 respondents (13.5%) reported moderate stress levels, 12 respondents (12.5%) reported severe stress levels, and 5 respondents (5.2%) reported very severe stress levels. The Chi Square test produced a p-value of 0.144. The results showed that there was no significant correlation (p=0.144) between exercise habits and stress levels among residents of Village X.